2002
DOI: 10.1016/s1352-2310(02)00579-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weather-type and long-range transport on airborne particle concentrations in Edinburgh, UK

Abstract: This study investigated the influence of regional-scale synoptic weather type and geographical source regions of air masses on two-particle concentration metrics (Black Smoke (BS) and PM10) in the city of Edinburgh, UK, between 1981 and 1996. Twenty-seven classifications of Jenkinson Daily Weather Types (JWT) were sub-divided into 9 directional categories and 3 vorticity categories, and the influence of JWT category on BS and PM10 determined. Four-day air mass back-trajectories for 1 July 1995-30 June 1996 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 16 publications
(17 reference statements)
3
46
0
Order By: Relevance
“…Few climate-changerelated studies have been conducted on PM. Buchanan et al (2002) examined the link between long-range transport of PM and meteorological patterns in Scotland, where they found no significant trends and some evidence that particle concentrations may decrease owing to decreased frequency of anticyclonic events.…”
Section: Extreme Value Methodsmentioning
confidence: 99%
“…Few climate-changerelated studies have been conducted on PM. Buchanan et al (2002) examined the link between long-range transport of PM and meteorological patterns in Scotland, where they found no significant trends and some evidence that particle concentrations may decrease owing to decreased frequency of anticyclonic events.…”
Section: Extreme Value Methodsmentioning
confidence: 99%
“…For example, Buchanan et al (2002) investigated the influence of regional weather patterns on PM 10 concentrations in Edinburgh, Scotland and demonstrated that PM can move well beyond its point source due to these large area dynamics. As climate change is predicted to affect synoptic-scale weather patterns, regional distribution of air pollutants may be affected.…”
Section: Altered Fate and Behavior Of Air Pollutantsmentioning
confidence: 99%
“…Lamb's daily types for the British Isles (since 1861) and the corresponding JC types (since 1880) can be found at http:// www.cru.uea.ac.uk/cru/data/lwt/. Uses and applications of JC in European regions, especially the north of the continent, can be found in Buishand and Brandsma (1997), Trigo and DaCamara (2000), Linderson (2001), Post et al (2002), Fowler and Kilsby (2002), Buchanan et al (2002), Antonsson et al (2008), Demuzere et al (2008), Post and Kärner (2008), etc. In other regions of the planet, the JC method has as yet been little used, although one of the first pilot applications was in a scope outside of the mid-latitudes, specifically in Egypt (Dessouky and Jenkinson, 1977).…”
Section: Introductionmentioning
confidence: 99%